2020
DOI: 10.1128/aac.02056-19
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into Plasmodium vivax Therapeutic Failure: CYP2D6 Activity and Time of Exposure to Malaria Modulate the Risk of Recurrence

Abstract: Plasmodium vivax relapse is one of the major causes of sustained global malaria transmission. Primaquine (PQ) is the only commercial drug available to prevent relapses, and its efficacy is dependent on metabolic activation by cytochrome P450 2D6 (CYP2D6). Impaired CYP2D6 function, caused by allelic polymorphisms, leads to the therapeutic failure of PQ as a radical cure for P. vivax malaria. Here, we hypothesized that the host immune response to malaria parasites modulates susceptibility to P. vivax recurrences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 67 publications
1
29
0
Order By: Relevance
“…Higher risk of malaria relapse and increased number of relapses were found in sporozoite-challenged volunteers with greatly reduced or absent CYP2D6 activity ( Bennett et al, 2013 ). Since then, a large body of evidence for an association between clinical failure of PQ and impaired CYP2D6 metabolism has accumulated ( Baird et al, 2018a , Baird et al, 2018b ; Brasil et al, 2018 ; Ingram et al, 2014 ; Silvino et al, 2016 , 2020 ).…”
Section: Natural Variation In Cytochrome P450 2d6 Activity and Metabomentioning
confidence: 99%
See 2 more Smart Citations
“…Higher risk of malaria relapse and increased number of relapses were found in sporozoite-challenged volunteers with greatly reduced or absent CYP2D6 activity ( Bennett et al, 2013 ). Since then, a large body of evidence for an association between clinical failure of PQ and impaired CYP2D6 metabolism has accumulated ( Baird et al, 2018a , Baird et al, 2018b ; Brasil et al, 2018 ; Ingram et al, 2014 ; Silvino et al, 2016 , 2020 ).…”
Section: Natural Variation In Cytochrome P450 2d6 Activity and Metabomentioning
confidence: 99%
“…Reduced CYP2D6 activity may represent a major confounder in therapeutic efficacy studies across malaria-endemic settings. Two cohort studies in the Amazon Basin of Brazil found 20–25% of individuals with impaired CYP2D6 enzyme (AS ≤ 1) ( Silvino et al, 2020 ), who had increased risk of P. vivax recurrence following CQ-PQ treatment after adjusting for confounding variables ( Silvino et al, 2016 , 2020 ). Nonimmune individuals with impaired enzyme activity were significantly more susceptible to P. vivax recurrence ( Silvino et al, 2020 ).…”
Section: Natural Variation In Cytochrome P450 2d6 Activity and Metabomentioning
confidence: 99%
See 1 more Smart Citation
“…Poor metabolizer (PM) phenotypes are defined by AS of 0, intermediate metabolizers (IM) are defined by AS from 0 to 1.25, normal metabolizers (NM) are defined by AS from 1.25 to 2.25, and ultrarapid metabolizers (UM) are defined by AS over 2.25 [ 38 ]. Recent studies, have established the importance of CYP2D6 polymorphisms on primaquine efficacy [ 24 27 , 47 ] showing associations between low-activity CYP2D6 phenotypes (poor and intermediate metabolizers) and P. vivax relapses. In the study of Bennett et al [ 24 ] two out of 25 patients relapsed after an initial P. vivax attack with correct chloroquine and primaquine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…CYP2D6 is responsible for the metabolism of 20–25% of clinically used drugs, and there are more than 46 known major CYP2D6 alleles which can be determined and predict a CYP2D6 phenotype of metabolization (poor, intermediate, normal and ultrarapid) [ 22 ]. It has been suggested that a reduced primaquine metabolism due to impairments in CYP2D6 function may be related to P. vivax relapses [ 24 27 ].…”
Section: Introductionmentioning
confidence: 99%